Differential Effects of Inhibitor Combinations on Lysophosphatidic Acid-Mediated Chemokine Secretion in Unprimed and Tumor Necrosis Factor-α-Primed Synovial Fibroblasts - Hui, Weili; Zhao, Chenqi; Bourgoin, Sylvain G. (Frontiers in Pharmacology, 2017)
Lysophosphatidic acid (LPA) is a pleiotropic bioactive lysophospholipid involved in inflammatory mediator synthesis. Signalling through p38MAPK, ERK, Rho kinase, and MSK-CREB contributes to LPA-mediated IL-8 production in fibroblast-like synoviocytes (FLS) from rheumatoid arthritis (RA) patients. The study was undertaken to investigate how LPA activates MSKs and how signalling crosstalk between TNFα and LPA contributes to the super-production of cytokines/chemokines. RAFLS pretreated or not with TNFα were stimulated with LPA. Immunoblotting with phospho-antibodies monitored MSK activation. Cytokine/chemokine production was measured using ELISA and multiplex immunoassays. LPA induced MSK activation by signalling through ERK whereas p38MAPK, Rho kinase, NF-κB or PI3K contribute to IL-8 synthesis mainly via MSK-independent pathways. Priming with TNFα enhanced LPA-mediated MSK phosphorylation and cytokine/chemokine production. After priming with TNFα, inhibition of ERK or MSK failed to attenuate LPA-mediated IL-8 synthesis even if the MSK-CREB signalling axis was completely or partially inhibited. In TNFα-primed cells, inhibition of LPA-mediated cytokine/chemokine synthesis required a specific combination of inhibitors such as p38MAPK and ERK for IL-8 and IL-6, and Rho kinase and NF-κB for MCP-1. The ability of the signalling inhibitors to block LPA induced cytokine/chemokine synthesis is dependent on the inflammatory cytokinic environment. In TNFα-primed RAFLS the super-production of IL-8 and IL-6 induced by LPA occurs mainly via MSK-independent pathways, and simultaneous inhibition of at least two MAPK signalling pathways was required to block their synthesis. Since simultaneous inhibition of both the p38MAPK and ERK-MSK-CREB pathways are required to significantly reduce LPA-mediated IL-8 and IL-6 production in TNFα-preconditioned RAFLS, drug combinations targeting these two pathways are potential new strategies to treat rheumatoid arthritis.